Engaging Citizens in Policy Making - Lember, Veiko; Randma-Liiv, Tiina (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a [CC BY-NC-ND 4.0] License. It is free to read, download and share on Elgaronline.com. Exploring academic and policy thinking on e-participation, this book opens up the organizational and institutional 'black box' and provides new insights into how public administrations in 15 European states have facilitated its implementation.